Integration of IFRS and FN-IB Applications, as Well as Their Influence on the Value of Iraqi Banks - Jameel Ahmed, Hayder; Wahhab, Asaad Mohammed Ali (Technium Social Sciences Journal, 2023)
This study aims to measure the impact on the value of banks in light of the integration of the application between the international financial reporting standards IFRS and the Financial Standard for Sustainability Accounting FN-IB, as well as the performance indicators of the banks in the research sample, using the impact and correlation model. Accordingly, the study was conducted on 12 Iraqi investment banks listed on the Iraq Stock Exchange (2015–2021), i.e., 84 notes (bank/year). The research variables were measured based on the models developed by the previous literature, where the effect of applying the International Financial Reporting Standards (IFRS) was measured by financial performance indicators (return on assets, return on equity, financial leverage, company size (total assets), and earnings per share "before the application year 2015 to 2021"). Hence, the FN-IB variable was measured as the percentage of disclosure of sustainability accounting information for investment banks according to the standards of investment banks FN-IB (18). The dependent variable, the company's value, was measured using the measurement model (Tobin's Q) for the study sample companies, in addition to measuring the effect of integration between the criteria for the two groups using multiple regression. In addition to the statistical methods to test the research hypotheses and find out the size of the correlation and the coefficient of determination using the statistical package for social sciences (SPSS) and the spreadsheet programme (Excel), The study results showed a correlation and effect between the integration of international financial reporting standards and FN-IB and company value. This relationship varies between positive, negative, strong, and medium. The inconsistency may be due to company size, management, and the cultural awareness of investors, customers, and regulators.